(untitled) (IAHS Medical Journal, 2024)
Background: Prediction and visual representation of developmental milestones of a growing fetus is most accurately done by ultrasonography. The present study was aimed to evaluate the correlation and accuracy of fetal foot length with fetal biparietal diameter to estimate fetal gestational age in Bangladeshi uncomplicated pregnant women of Chattogram district. Materials and methods: This cross-sectional observational study was conducted on 200 uncomplicated pregnant women of 15th to 28th weeks of gestation during the period from October 2021 to September 2022 in the Department of Anatomy, Chittagong Medical College, Chattogram. Fetal biometric parameters such as fetal foot length and biparietal diameter were measured by ultrasonography. For statistical analysis, Pearson’s correlation test and correlation-regression analysis was done and p-value was considered significant if it was <0.05 at 95% level of confidence. Results: Pearson’s correlation test showed that gestational age had strong positive and highly significant (p=0.000) correlation with both fetal foot length and biparietal diameter. The relation between gestational age and fetal foot length(r=0.986) is less strong than the relation between gestational age and biparietal diameter(r=0.988). Conclusion: This study revealed relationship between fetal foot length and gestational age regarding accuracy. Ultrasonographic measurement of fetal foot length can be practiced alongside traditional biometric parameters for pregnancy dating in modern medical science. IAHS Medical Journal Vol 6(2), December 2023; 35-39